Implementation of homework in an urban primary school in Malaysia / Ezareen C. Ahmad Ezanee - C. Ahmad Ezanee, Ezareen (2007)
The issue of homework is relatively new in Malaysia. The crucial reason for this case study came as a result of a study that concluded Malaysian students spend a lot of time completing homework as compared to other countries. Hence, the Education Ministry pioneered homework circular to provide guidelines to homework implementation for all schools. The case study was conducted in an urban primary school to investigate the current homework practices and implementation in this school. The aims of this case study was to look and to examine the real situation of homework implementation in schools in terms of the level of adherence prior to the circular homework and after the circular had been disseminated as stipulated by the Ministry of Education, 2004. In addition, the case study investigated what were the students’ and teachers’ opinion of homework. The objective of this case study was to look at the current homework practices and implementation in the areas of roles of teachers, types of homework, amount of homework, time spent on homework, and punishment. It was also to find out the students responses about homework in the areas of role of the family, homework problem, value of homework, difficulty of homework, homework completion and home environment. The research instruments used for data collection were survey questionnaire and interview sessions with students and teachers. The findings of the study reported that the school and teacher had adhered to the implementation of homework circular. Secondly, students were keen to do homework and were highly motivated to complete homework. Even if they did not understand the exact function of homework but students believed that homework made them smarter; learn good study habits and made them prepare for tests and examination. In light of the findings all stakeholders involved could perhaps plan an effective way on how to enhance the interest of students and parents to become actively involved and facilitate their child in homework problems. It is recommended that possibly an innovation of a homework guide or homework modules be made that best suit the needs of students and to facilitate teachers on how best to approach homework.